First person - Eileen Lynch (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Eileen Lynch is first author on 'C9ORF72-related cellular pathology in skeletal myocytes derived from ALS-patient induced pluripotent stem cells', published in DMM. Eileen is a graduate research assistant/PhD candidate in the lab of Masatoshi Suzuki at University of Wisconsin-Madison, WI, USA, investigating in vitro disease modeling of neuromuscular diseases.